PERAN KEPALA MADRASAH DALAM PENGELOLAAN PROGRAM KARTU INDONESIA PINTAR (KIP) UNTUK PENINGKATAN MUTU PNDIDIKAN DI MADRASAH ALIYAH NU MARON - Taupiq Dian Saputra; Ismatul Izzah; Sollah Solehudin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to examine the role of the madrasah principal in managing the Smart Indonesia Card (KIP) Program and its contribution to improving the quality of education at Madrasah Aliyah NU Maron. The KIP Program is a government initiative aimed at expanding access to education for students from underprivileged families. In its implementation, the madrasah principal plays a crucial role in the planning, implementation, monitoring, and evaluation of the program. This research method uses a qualitative approach through case studies. Data collection was conducted through interviews, observations, and document collection. The research findings indicate that the madrasah principal functions as a manager, leader, and supervisor to ensure the KIP program is implemented effectively and according to its objectives. In addition, the madrasah principal also plays a role in increasing transparency and accountability in the management of KIP funds. Effective management of the KIP program has been shown to have positive effects on improving the quality of education, such as increased student participation, decreased dropout rates, and increased student enthusiasm for learning. Therefore, the active role and capabilities of the madrasah principal are crucial elements in optimizing the implementation of the KIP program to support improved educational quality in madrasah.